Penanda infeksi bakteri pada pneumonia anak - Wardah .; Nurjannah .; Bakhtiar .; Rini Savitri Daulay (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
Pneumonia is the main health problem and the major causes of children’s death, particularly in children under five years old. Etiology of pneumonia are varried but it is very difficult to identify the etiology of pneumonia in children. The examination of lung’s secretory is very difficult to be performed in children. The examination of leucocyte, erythrocyte sedimentation rate, C-reactive protein and procalcitonin level can be used as bacterial infection’s marker to be treated with antibiotics. In addition, procalcitonin clinically proven more sensitive and spesific to identifying the infection caused by bacteria, compare to another marker.Keywords : pneumonia; children; marker; procalcitonin